USABILITY ENGINEERING METHODS FOR SOFTWARE DEVELOPERS. - Holzinger, Andreas (Communications of the ACM, 2005)
The article discusses usability engineering methods for software practitioners. The human-computer interaction community aims to increase the awareness and acceptance of established methods among software practitioners. Ease of use affects the users' performance and their satisfaction, while acceptability affects whether the product is used. Thus, it is of great importance that every software practitioner not only be aware of various usability methods, but be able to quickly determine which method is best suited to every situation in a software project. One of the basic lessons we have learned in human-computer interaction is that usability must be considered before prototyping takes place. It is generally accepted that the following five essential usability characteristics should be part of any software project: learnability, so the user can rapidly begin working with the system efficiently, enabling a user who has learned the system to attain a high level of productivity; memorability, allowing the casual user to return to the system after a period of non-use without having to relearn everything; low error rate, so users make fewer and easily rectifiable errors while using the system and no catastrophic errors occur and satisfaction, making the system pleasant to use.